Visual network research (VNR) – a theoretical and methodological appraisal of an evolving field. Issue 4 (7th August 2020) - Gamper, Markus; Schönhuth, Michael
Abstract : Visualisation has always played an important role in social network analyses. Most illustrations are used for the representation of research results and are made with the help of mathematical algorithms. In the last decades, a new movement, coming from the egocentric-qualitative network analyses, uses visualisation not only for results presentations but also for qualitative as well quantitative data collection and validation. This is a very heterogenic field, which uses diverse procedures and tools in its data collection process, which have yet to be systematically analysed. The connection to the theoretic concept is still in its infancy and systematic compilation of best practice examples have only been described rudimentarily. In this article the image of the 'visual network' movement will be systematically traced and structured, thereby the movement is linked to the 'relational sociology'. Advantages and disadvantages of the visual instruments are discussed. Finally, visual items (e.g. concentric circles, sectors) for the presented of information during the visual data collection are under consideration. This article offers terminologies for different kind of visual data collection procedures and based on best practice examples, the article aims to provide guidance for practical implementation of visual tools in this kind of network research.